2000
DOI: 10.1017/s0031182000006831
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among Brazilian Biomphalaria species (Mollusca: Planorbidae) based upon analysis of ribosomal ITS2 sequences

Abstract: In spite of their abundance, widespread distribution and medical importance, the phylogenetic relationships among Biomphalaria snails have received relatively little attention. We have collected and studied 29 populations of snails obtained from different localities from Brazil. We have sequenced the ribosomal DNA second internal transcribed spacer (ITS2) from the following Biomphalaria species: B. glabrata, B. tenagophila tenagophila, B. occidentalis, B. straminea, B. peregrina, B. kuhniana, B. schrammi, B. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 16 publications
3
43
0
2
Order By: Relevance
“…It was very clear the close relationship between B. straminea and B. kuhniana, and despite the morphological similarity of B. straminea and B. intermedia with B. peregrina, it could not be included in the complex, which is supported by the morphological information reported by Paraense (1988). Following this, Vidigal et al (2000b), through the sequencing of ITS2 of rRNA of the ten Brazilian Biomphalaria species, confirmed that B. kuhniana (from Venezuela and Brazil) is more closely related with B. straminea (from Brazil) than with B. intermedia (from Brazil). Afterwards, Dejong et al (2001) observed that, among the 23 Biomphalaria species studied, the most closely related group was that formed by B. straminea (Brazil), B. kuhniana (Dominica, Colombia and Venezuela) and B. intermedia (Paraguay).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It was very clear the close relationship between B. straminea and B. kuhniana, and despite the morphological similarity of B. straminea and B. intermedia with B. peregrina, it could not be included in the complex, which is supported by the morphological information reported by Paraense (1988). Following this, Vidigal et al (2000b), through the sequencing of ITS2 of rRNA of the ten Brazilian Biomphalaria species, confirmed that B. kuhniana (from Venezuela and Brazil) is more closely related with B. straminea (from Brazil) than with B. intermedia (from Brazil). Afterwards, Dejong et al (2001) observed that, among the 23 Biomphalaria species studied, the most closely related group was that formed by B. straminea (Brazil), B. kuhniana (Dominica, Colombia and Venezuela) and B. intermedia (Paraguay).…”
Section: Discussionsupporting
confidence: 72%
“…However, the Colombian specimens showed only one of the three profiles, reported by Vidigal (2000a), which mirrors less polymorphism when compared with Brazilian specimens. The phylogenetic relationship of B. amazonica, obtained through sequencing analyses by Vidigal et al (2000b) and DeJong et al (2001), with species of the same genus, from Neotropical and African regions, showed that B. amazonica possesses high affinity with the species of the complex B. straminea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphological variations found in the samples analysed in this study are listed in the Table. Although Paraense (1966) previously described the morphologies of B. amazonica and B. cousini, the author emphasized the difficulties involved in such classifications, which were primarily due to high degrees of similarity between the two species. Likewise, high degrees of similarity between various Biomphalaria species were also described in phylogenetic studies performed by Vidigal et al (2000b). Those studies demonstrated that the branch with B. amazonica specimens always divided into two clusters that were similar but distinct.…”
mentioning
confidence: 79%
“…The present study was aimed at designing specific primers for Brazilian snail hosts of S. mansoni from available sequences of ITS2 of the ribosomal RNA gene, sequenced by Vidigal et al (2000a), for phylogenetic studies on Brazilian Biomphalaria.…”
mentioning
confidence: 99%